2019
DOI: 10.1101/803890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell multiomics sequencing reveals the functional regulatory landscape of early embryos

Abstract: 17Extensive epigenetic reprogramming occurs during preimplantation embryo development and is 18 accompanied by zygotic genome activation (ZGA) and first cell fate specification. Recent studies 19 using single-cell epigenome sequencing techniques have provided global views of the dynamics of 20 different epigenetic layers during this period. However, it remains largely unclear how the drastic 21 epigenetic reprogramming contributes to transcriptional regulatory network. Here, we developed a 22 single-cell multi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Recent advances in experimental multi-omics technologies have increased the availability of paired data [8][9][10][11]30 . While most of the current simultaneous multi-omics protocols still suffer from lower data quality or throughput than that of single-omics methods 54 , paired cells can be highly informative in anchoring different omics layers and should be utilized in conjunction with unpaired cells whenever available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in experimental multi-omics technologies have increased the availability of paired data [8][9][10][11]30 . While most of the current simultaneous multi-omics protocols still suffer from lower data quality or throughput than that of single-omics methods 54 , paired cells can be highly informative in anchoring different omics layers and should be utilized in conjunction with unpaired cells whenever available.…”
Section: Discussionmentioning
confidence: 99%
“…While simultaneous assays are emerging recently [8][9][10][11] , different omics are usually measured independently and produce unpaired data, which calls for effective and efficient in silico multi-omics integration 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Single‐nucleus chromatin accessibility and mRNA expression sequencing can also be used to understand gene regulation, as this technology provides high‐throughput sequencing of the transcriptome and chromatin accessibility in the same cell 49 . Other advances can be applied for a different problem of characterizing molecular cell state, and include those utilizing transcriptomics (mRNA) as one of its modalities, in addition to either DNA, 50 protein expression, 10,51 chromatin accessibility 52,53 or DNA methylation 54–57 . Lineage tracing of immune cells that do not carry a natural bar code, such as TCR or B‐cell receptor, can also benefit from recent technologies using synthetic barcodes, such as CellTagging which uses a lentiviral approach 58 .…”
Section: Discussionmentioning
confidence: 99%
“…3a, e). Chromatin accessibility of cis-regulatory sequences drives cell differentiation and zygotic genome activation (ZGA) by regulating gene expression in early mammalian embryos [7][8][9]13 . Studies have shown that post-translational modi cations, such as histone acetylation and ubiquitination, enhance chromatin accessibility by disrupting chromatin folding and globule formation 47,48 .…”
Section: Discussionmentioning
confidence: 99%